Challenges with couples, serodiscordance and HIV disclosure: healthcare provider perspectives on delivering safer conception services for HIV‐affected couples, South Africa. Issue 2 (12th March 2014) - Crankshaw, Tamaryn L; Mindry, Deborah; Munthree, Chantal; Letsoalo, Thabo; Maharaj, Pranitha
Abstract : Introduction: Introduction Safer conception interventions should ideally involve both members of an HIV‐affected couple. With serodiscordant couples, healthcare providers will need to manage periconception risk behaviour as well tailor safer conception strategies according to available resources and the HIV status of each partner. Prior to widespread implementation of safer conception services, it is crucial to better understand provider perspectives regarding provision of care since they will be pivotal to the successful delivery of safer conception. This paper reports on findings from a qualitative study exploring the viewpoints and experiences of doctors, nurses, and lay counsellors on safer conception care in a rural and in an urban setting in Durban, South Africa. Methods: We conducted six semistructured individual interviews per site (a total of 12 interviews) as well as a focus group discussion at each clinic site (a total of 13 additional participants). All interviews were coded in Atlas.ti using a grounded theory approach to develop codes and to identify core themes and subthemes in the data. Results: Managing the clinical and relationship complexities related to serodiscordant couples wishing to conceive was flagged as a concern by all categories of health providers. Providers added that, in the HIV clinical setting, they often found it difficult to balance their professional priorities, to maintain the health of their clients, and to ensure that partners were not exposed to unnecessary risk, while still supporting their clients' desires to have a child. Many providers expressed concern over issues related to disclosure of HIV status between partners, particularly when managing couples where one partner was not aware of the other's status and expressed the desire for a child. Provider experiences were that female clients most often sought out care, and it was difficult to reach the male partner to include him in the consultation. Conclusions: Providers require support in dealing with HIV disclosure issues and in becoming more confident in dealing with couples and serodiscordance. Prior to implementing safer conception programmes, focused training is needed for healthcare professionals to address some of the ethical and relationship issues that are critical in the context of safer conception care.